(untitled) (Research, Society and Development, 2020)
Purpose of the present study was to analyze the curricula of the professional formation in Physical Education in Amazonas and professional profile of lectures who teach gymnastic subjects. Therefore, were analyzed eight curricula of the professional formation in Physical Education of main institutions of higher education in Amazonas and the Lattes curricula of ten university lecturers who teach gymnastics in the Physical Education undergraduate courses in the second semester of 2019. From the data obtained, we verified curricular grids need updating as to the nomenclature of gymnastics, and two institutions included disciplines of gymnastics in their undergraduate curriculum. Most lecturers were female, and although everyone had a specialization, only three were in gymnastics. The same happened in the stricto-sensu graduate program in which the minority turned their studies to gymnastic content. This low production in gymnastics identified by the lack of projects and guidelines, since only two university professors have research and extension projects in the area. Finally, we hope that these data can support reflections on the performance and training of university teachers in the gym area in the State of Amazonas, in addition to assisting in future research.